Про причини та наслідки диктатури - Мороз, М. Ю. (ХНУРЕ, 2023)
This work is devoted to the study of the nature of dictatorship. Particular attention is paid to the reasons for such a regime and its consequences for the state. The author examines the factors contributing to the emergence of dictators, such as economic crisis, political instability, social unrest, analyzes their impact on non-authoritarian rule in society, in particular, the erosion of civil liberties, suppression of dissent and human rights violations. The work aims to deepen our understanding of the forces that drive dictatorship and shed light on the complex and often devastating consequences of dictatorial rule.